MENJEMBATANI AKSESIBILITAS MASYARAKAT MISKIN PADA PELAYANAN KESEHATAN MELALUI INSTITUSI LOKAL - Ahmad Arif Widianto (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2013)
The lack of the Poor’s accessibility to the health care is still become a problem that difficult to resolved. In practice, they still face obstacles that hinder their accessibility to the health services. Some literatures suggest that the problem is caused by two factors. The first is the internal factors (come from the individuals themselves); such as the lack of people`s participation in health service activities. The second one is the external factors (come from outside the individual); such as geographical location, discrimination, and administrative procedures. However, in my opinion, these factors are not the most substantial and fundamental causes; they more like “secondary” factors. This paper assumes that the lack of poor`s accessibility to health services caused by systemic and structural factors: it is the technocratic models of the policies applied by the government (top-down) in the healthcare development that negated the potential of local communities. The Society has no chance to express their aspirations related to the good form of health care that they want. In addition, they were not involved in the process of formulation, implementation, monitoring, and evaluation of government’s health policies. The result is the implementation of health development at the practical level experienced many obstacles and unpredictable problems, including the problem of the poor`s low accessibility to the health services and so on dependency. Thus, the poor become powerless to access health services. Therefore, it needs a medium that bridges the poor’s access to the health services, which is called. These points will be discussed in this paper. The goal of the paper is to reveal the systemic and structural obstacles that obstruct the poor’s access to health services. Moreover, this paper offers an alternative solution to solve this problem by using the local institutions as a medium that facilitate the poor to access the health services.